Revisiting Drug Development Against the Neglected Tropical Disease, Amebiasis - Shrivastav, Manish T.; Malik, Zainab; Somlata, (Frontiers in Cellular and Infection Microbiology, 2021)
Amebiasis is a neglected tropical disease which is caused by the protozoan parasite Entamoeba histolytica. This disease is one of the leading causes of diarrhea globally, affecting largely impoverished residents in developing countries. Amebiasis also remains one of the top causes of gastrointestinal diseases in returning international travellers. Despite having many side effects, metronidazole remains the drug of choice as an amebicidal tissue-active agent. However, emergence of metronidazole resistance in pathogens having similar anaerobic metabolism and also in laboratory strains of E. histolytica has necessitated the identification and development of new drug targets and therapeutic strategies against the parasite. Recent research in the field of amebiasis has led to a better understanding of the parasite’s metabolic and cellular pathways and hence has been useful in identifying new drug targets. On the other hand, new molecules effective against amebiasis have been mined by modifying available compounds, thereby increasing their potency and efficacy and also by repurposing existing approved drugs. This review aims at compiling and examining up to date information on promising drug targets and drug molecules for the treatment of amebiasis.